THE IMPLICATIONS OF A CORPUS-BASED APPROACH TO SPECIALIZED VOCABULARY IN ENGLISH FOR ISLAMIC STUDIES AT THE UNIVERSITY LEVEL - Sardian Maharani Asnur; Syahruni Junaid; Muhammad Jafar; Ahmad Mustamir Waris (International Conference on Social and Islamic Studies, 2021)
The objective of this study is to define the implication of teaching English for Islamic Studies (EIS) course based specialized corpora into university-level for nonnative speakers of English. The EIS course is one of additional course for the first year students in Islamic university especially in Universitas Islam Negeri Alauddin Makassar, Indonesia. A corpora of English for Islamic Studies were compiled from literature used in English for Islamic Studies. The vocabulary compositions and lexical density were examined and arranged in the form of Bilingual Glossary of Islamic Studies (BiGIS). The results of this study imply that the use of corpus is very useful for studying contexts where words that have identical meanings are usually used so as to avoid unwanted connotations. In relation to teaching English for Islamic studies, the corpus can be an effective learning medium. A lot of information not found in dictionaries can be learned using the corpus available in the BiGIS.